Bootstrapping impulse responses in VAR analyses - Helmut Lütkepohl (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Because the parameters of vector autoregressive processes are often difficult to interpret directly, econometricians use quantities derived from the parameters to disentangle the relationships between the variables. Bootstrap methods are often used for inference on the derived quantities. Alternative bootstrap methods for this purpose are discussed, some related problems are pointed out and proposals are presented to overcome the difficulties at least partly. Some remaining problems are presented.
urn:nbn:de:kobv:11-10047285
Keywords: 330; Impulse response; bootstrap; vector autoregression; confidence interval